2020
DOI: 10.2478/raon-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three film analysis softwares using EBT2 and EBT3 films in radiotherapy

Abstract: Introduction The purpose of the study was to compare the results of gamma value based film analysis according to the used type of self-developer film and software product. Material and methods The films were irradiated with different treatment techniques such as 3D conformal and intensity modulated radiotherapy with static and rotational delivery. Stereotactic plans with conformal and intensity modulated arc techniques, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Conventionally segmented mode is generally adopted for glioblastoma radiotherapy. Thus, taking the 3%/3 mm criteria as the standard to evaluate the consistency of the two dose distributions is generally accepted in clinical practice [22][23][24] . In other words, even when the number of wrapped electrodes reaches twelve, the distortion of the deep-site dose distribution is still small.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally segmented mode is generally adopted for glioblastoma radiotherapy. Thus, taking the 3%/3 mm criteria as the standard to evaluate the consistency of the two dose distributions is generally accepted in clinical practice [22][23][24] . In other words, even when the number of wrapped electrodes reaches twelve, the distortion of the deep-site dose distribution is still small.…”
Section: Discussionmentioning
confidence: 99%
“…Their characterization of the absolute change in netOD over time showed that film irradiated to higher doses had a greater absolute change in netOD over time. Pocza et al 22 . evaluated darkening long‐term of EBT2 film after irradiation to up to 2 Gy and found that OD increased by up to 15% for films scanned with the red channel at 18 months after irradiation relative to the original scan at 24 h. Fuss et al 23 .…”
Section: Discussionmentioning
confidence: 99%
“…21 Their characterization of the absolute change in netOD over time showed that film irradiated to higher doses had a greater absolute change in netOD over time. Pocza et al 22 evaluated darkening long-term of EBT2 film after irradiation to up to 2 Gy and found that OD increased by up to 15% for films scanned with the red channel at 18 months after irradiation relative to the original scan at 24 h. Fuss et al 23 reported that EBT film irradiated to 0.9-8.1 Gy and scanned 4 months later showed a 5.4%-12.4% increase in netOD relative to the netOD measured at 24 h. From these data, we can conclude that beyond 24 h, the extent of darkening in irradiated film is less severe than during the first few hours after irradiation. However, we found that the netOD continued to increase beyond 24 h (Figure 1) and that this will continue for several months after irradiation (Figure 2).…”
Section: Long-term Evaluationmentioning
confidence: 99%
“…The user experience varies signi cantly among each software, making a comparison valuable. To date, there has been limited investigation into comparing RCF software [5]. Such a comparison is bene cial, as RCF is commonly employed by radiotherapy departments for stereotactic PSQA.…”
Section: Couch Motion Errorsmentioning
confidence: 99%